Experimental validation of a nuclear forensics methodology for source reactor-type discrimination of chemically separated plutonium - Jeremy M. Osborn; Kevin J. Glennon; Evans D. Kitcher; Jonathan D. Burns; Charles M. Folden, III; Sunil S. Chirayath (Nuclear Engineering and Technology, 2019)
An experimental validation of a nuclear forensics methodology for the source reactor-type discrimination of separated weapons-useable plutonium is presented. The methodology uses measured values of intra-element isotope ratios of plutonium and fission product contaminants. MCNP radiation transport codes were used for various reactor core modeling and fuel burnup simulations. A reactor-dependent library of intra-element isotope ratio values as a function of burnup and time since irradiation was created from the simulation results. The experimental validation of the methodology was achieved by performing two low-burnup experimental irradiations, resulting in distinct fuel samples containing sub-milligram quantities of weapons-useable plutonium. The irradiated samples were subjected to gamma and mass spectrometry to measure several intra-element isotope ratios. For each reactor in the library, a maximum likelihood calculation was utilized to compare the measured and simulated intra-element isotope ratio values, producing a likelihood value which is proportional to the probability of observing the measured ratio values, given a particular reactor in the library. The measured intra-element isotope ratio values of both irradiated samples and its comparison with the simulation predictions using maximum likelihood analyses are presented. The analyses validate the nuclear forensics methodology developed. Keywords: Nuclear forensics, Reactor-type discrimination, Weapons-useable plutonium, Intra-element isotope ratios, Maximum likelihood